2021
DOI: 10.5713/ajas.20.0246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with Allium mongolicum Regel extracts on growth performance, carcass characteristics, and the fat color and flavor-related branched-chain fatty acids concentration in ram lambs

Abstract: Objective: This study aimed to investigate the effect of dietary supplementation with Allium mongolicum Regel extracts on the growth performance, carcass characteristics, fat color, and concentrations of three branched-chain fatty acids related to flavor in ram lambs. Methods: Sixty 3-month-old, male, small-tailed Han sheep were selected and randomly allocated into four groups in a randomized block design. Four feeding treatments were used: 1) a basal diet without supplementation as the control group (CK); 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…As hypothesized, AME significantly decreased ( P < 0.05) the concentrations of MOA and MNA in the liver. Our findings were similar to the results of Liu et al (2019) and Liu and Ao (2021) , who found that supplementation with flavonoids and ethanol extract in the diet of Small-tailed Han sheep significantly decreased the concentrations of MOA and EOA in the Longissimus dorsi muscle and Dorsal subcutaneous , Omental , and Perirenal adipose tissues. In the present study, there was no difference in the concentration of EOA in the livers of lambs between the CON group and the AME group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As hypothesized, AME significantly decreased ( P < 0.05) the concentrations of MOA and MNA in the liver. Our findings were similar to the results of Liu et al (2019) and Liu and Ao (2021) , who found that supplementation with flavonoids and ethanol extract in the diet of Small-tailed Han sheep significantly decreased the concentrations of MOA and EOA in the Longissimus dorsi muscle and Dorsal subcutaneous , Omental , and Perirenal adipose tissues. In the present study, there was no difference in the concentration of EOA in the livers of lambs between the CON group and the AME group.…”
Section: Discussionsupporting
confidence: 92%
“…Allium mongolicum Regel contains polysaccharides, flavonoids, polyphenols, and other bioactivators ( Li et al, 2019 ). Our previous studies indicated that A. mongolicum Regel ethanol extract ( AME ) significantly decreased the concentration of BCFAs in the Longissimus dorsi muscle and Dorsal subcutaneous , Omental , and Perirenal adipose tissues of Small-tailed Han sheep ( Liu et al, 2019 ; Liu and Ao, 2021 ). However, the molecular mechanism of this effect has not yet been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…According to many years of experience of local herders, the growth rate of sheep after eating A. mongolicum is accelerated, the incidence of disease is reduced, and the quality and flavor of meat can be significantly improved ( 93 – 95 ). Ao et al have conducted long-term research on the application of A. mongolicum to the mutton industry ( 96 , 97 ). The addition of A. mongolicum polysaccharides and A. mongolicum total flavonoids in the diet proves that A. mongolicum and its extracts can effectively improve the growth performance, antioxidant status, and immune response of lamb, while improving meat quality.…”
Section: Feed Additivesmentioning
confidence: 99%
“…A. Mongolicum Regel contains polysaccharides, flavonoids, polyphenols, and other bioactive compounds ( Li et al, 2019 ). Our previous studies indicated that A. Mongolicum Regel ethanol extract (AME) significantly decreased the concentration of BCFAs in the longissimus dorsi muscle and dorsal subcutaneous, omental and perirenal adipose tissues of Small-tailed Han sheep ( Liu et al, 2019 ; Liu and Ao, 2021 ). However, it is not clear whether AME affects the synthesis of three BCFAs related to flavor in the rumen of lambs.…”
Section: Introductionmentioning
confidence: 99%